al-Amanah as a foundational Qur’anic principle in daily human affairs - Islam, Md. Sirajul; Osmani, Noor Mohammad; Nurunnabi, Mohammad (IIUM Press, 2025)
This study underscores the significance of al-amānah as a vital concept for promoting social justice and ethical conduct within communities. Al-amānah (trustworthiness or honesty) is a fundamental directive from Allāh Subḥānahu Wa-Taʿālā (Glorified and Exalted). Upholding al-amānah serves as a cornerstone for fulfilling the rights ordained by Almighty Allāh and His Messenger, as well as safeguarding human rights. Despite its centrality, many individuals neglect to observe al-amānah in their daily lives, a failure that contributes to widespread corruption, violence, and anti-social behaviour across societies worldwide. The primary aim of this study is to explore the essential role of al-amānah in human life and its implications for social order. By recognising and emphasising the importance of al-amānah, this research highlights its pivotal role in establishing an ideal society—one characterised by the faithful observance of the rights of Almighty Allāh, the Messenger, and the rightful claims of every individual.